Posterior Reversible Encephalopathy Syndrome Associated With Anlotinib: A Case Report and Literature Review - Nan, Di; Yin, Xiang; Ma, Di; Jiang, Xiaoyu; Wu, Baihua; Feng, Jiachun (Frontiers in Neurology, 2021)
Posterior reversible encephalopathy syndrome (PRES) is a relatively rare clinical disease, characterized by reversible subcortical vasogenic edema. Here, we present the first reported case of PRES induced by anlotinib, a multi-target tyrosine kinase inhibitor. A 56-year-old female patient with lung adenocarcinoma and bone metastasis experienced hypertension and mental confusion when she received anti-angiogenesis treatment. PRES was diagnosed after magnetic resonance of the patient’s brain revealed hyperintensities bilaterally around the cerebellum, pons, fronto-parieto-occipital areas, and corona radiate. Diffusion-weighted imaging showed hyperintensities bilaterally in the parieto-occipital cortical regions. Subsequently, the patient was diagnosed with PRES, and remission was achieved with anti-hypertensive drugs. Six cases of rare adverse effects induced by anlotinib were reviewed in the literature. Since anlotinib has been widely applied as a novel third-line treatment in patients with non-small-cell lung cancer, the association between PRES and anlotinib would benefit neurologists and oncologists in future diagnoses and treatment.